Impacts of Deforestation and Climate Variability on Terrestrial Evapotranspiration in Subarctic China - Yunjun Yao; Shunlin Liang; Jie Cheng; Yi Lin; Kun Jia; Meng Liu (Forests, 2014)
Although deforestation affects hydrological and climatic variables over tropical regions, its actual contributions to changes in evapotranspiration (ET) over subarctic China remain unknown. To establish a quantitative relationship between deforestation and terrestrial ET variations, we estimated ET using a semi-empirical Penman (SEMI-PM) algorithm driven by meteorological and satellite data at both local and regional scales. The results indicate that the estimated ET can be used to analyse the observed inter-annual variations. There is a statistically significant positive relationship between local-scale forest cover changes (∆F) and annual ET variations (∆ET) of the following form: ∆ET = 0.0377∆F – 2.11 (R2 = 0.43, p < 0.05). This relationship may be due to deforestation-induced increases in surface albedo and a reduction in the fractional vegetation cover (FVC). However, the El Niño/Southern Oscillation (ENSO), rather than deforestation, dominates the multi-decadal ET variability due to regional-scale wind speed changes, but the exact effects of deforestation and ENSO on ET are challenging to quantify.